Rekrutmen dan Seleksi Berbasis Kebutuhan Pada Lembaga Pendidikan - Fajri Dwiyama (Institusi Agama Islam Negeri (IAIN) Bone, 2023)
Recruitment is the process of gathering prospective office holders who have certain qualificationsfor jobs in an organization or industry. There are two methods used in recruitment, namely theopen recruitment method and the closed method. Employee selection is an important process ineducational institutions to obtain competent and productive employees. The steps that need to betaken in employee selection include: analyzing job needs, developing selection criteria,determining selection methods, carrying out the selection process, making selection decisions, andmonitoring and evaluating selection. By applying these principles, educational institutions canincrease accuracy in getting the best, competent employees so they can provide optimalperformance and productivity.